Effect of 1-MCP treatment on preservation and quality of 'Jinyan' kiwifruit. Issue 6 (May 2019) - Tang, Fuyi; Li, Weijia; Wang, Tie; Wang, Jun; Li, Longjun; Deng, Qunxian
Abstract: The experiment is carried out with the 'Jinyan' kiwifruit planted in Pujiang City, in the Sichuan Province as a test material. Under the sealed condition of PE fresh-keeping bag, the effect of different concentrations of 1-MCP on the storage and preservation of 'Jinyan' kiwifruit is studied. The result shows that under the normal temperature storage condition, the suitable concentration of 1-MCP can slow down the fruit hardness of 'Jinyan' kiwifruit during storage, reduce the rot rate and water loss rate, and make 'Jinyan' kiwifruit in storage process. Maintain high soluble solid content, inhibit the decrease of titratable acid content and VC content, prolong the storage time of 'Jinyan' kiwifruit, and effectively maintain the physiological quality of 'Jinyan' kiwifruit. Among them, 1-MCP perform best in the storage and preservation of 'Jinyan' kiwifruit at a concentration of 375 mg⋅L −1 .